INFLUENCE OF PLANT BIOMETRICS ON BIOMASS YIELD OF INTRODUCED RARE ENERGY CROPS - Rozhko, I.; D’omin, D.; Kulyk, M. (Scientific Progress & Innovations, 2021)
The involvement of rare energy crops into cultivation is highly important in the context of obtaining an additional energy resource – the biomass of these plants. Solid, liquid and gaseous biofuels are produced from plant raw materials of energy crops, and their use will reduce the energy dependence of local communities. The study of their morphological and biological traits is another important issue that will enable to identify the peculiarities of yield formation and find effective ways to manage energy crop areas. Therefore, the aim of our research was to provide morphological and biological characteristics of plants and to reveal the peculiarities of biomass formation of rare energy crops. Observations and analyses based on the monographic method, data from dictionaries and reference books as well as the authors’ own work and scientific publications of both Ukrainian and foreign scientists were used for this purpose. Authorized scientific methods, DSTU and methods of research in agronomy were used in the laboratory and field experiments. The results of multi-year research made it possible to establish the variability of biometric indicators of energy crops: Indian grass (Sorghastrum nutans (L.) Nash), Big Bluestem (Andropogon Gerardii Vitman) and Columbus grass (Sorghum Almum Parodi). The highest height and plant stem density are formed by Indian grass and Columbus grass. The interdependence between the quantitative indicators of plants of rare energy crops has been determined: as the height of plants increases, their number and biomass yield increases. The highest yield of dry biomass is formed by Columbus grass and Indian grass, 8.0 and 5.0 t/ha, respectively. This indicator is significantly lower in Big Bluestem – at a level of 2.3 t/ha. It has been established that the biometric indices of plants in height and plant stem density have a significant impact on the level of biomass yield of the studied energy crops. This is confirmed by a strong rectilinear correlation (r>0.71) and multidimensional relationship, and is described by the following equation: z = – 2.7247 + 0.0664 × x - 0.0103 × y. Prospects for further research will be to study the seed productivity of rare energy crops depending on growing conditions.